Contamination Level of Staphylococcus spp. in Raw Goat Milk and Associated Risk Factors - E Taufik; G Hildebrandt; J N Kleer; T I Wirjantoro; K Kreausukon; F H Pasaribu (Media Peternakan, 2008)
This study was aimed to investigate the presence of pathogenic bacteria in raw goat milk by using Staphylococcus spp. as indicator bacteria, and also to evaluate the potential risk factors associated with them. Information regarding potential risk factors was collected by questionnaire. The conventional bacteriological method for bacterial isolation and the indirect test (California Mastitis Test (CMT)) for determining udder inflammation status were employed. A sample size of 300 udder halves milk samples from three commercial dairy goat farms in the Bogor District, West Java Province, Indonesia were investigated for counts and prevalence of indicator bacteria. Ten potential risk factors were also evaluated in relation to counts and prevalence of indicator bacteria. The results showed that the median value of indicator bacterial count from overall udder-half milk samples was 3.00 log cfu/ml. The indicator bacterial count from udder-half milk samples was significantly different (P < 0.05) among farms. Overall prevalence of Staphylococcus spp. was 78.7%. As one of potential risk factors, udder inflammation status was found to be risk factor for Staphylococcus spp. contamination in milk. Udders with inflammation had significant association and a higher chance of having contaminated samples by Staphylococcus spp. as compared to udders without inflammation. Additionally, according to these study results, CMT can be used as an effective, reliable, cheap and “farm and farmer friendly test" for screening test of intramammary infection (IMI) or sub clinical mastitis in dairy goats. Key words: goat milk, Staphylococcus spp., prevalence, risk factor, California Mastitis Test